Inside Jewish Day Schools : Leadership, Learning, and Community - Pomson, Alex; Wertheimer, Jack (Book collections on Project MUSE., 2022)
"This book takes readers inside Jewish day schools to observe what they actually do. Many different types of Jewish day schools exist, and the variations are not well understood. Nor is much information available about how day schools function. This volume is conceived as a guide to those wishing to understand the contemporary Jewish day school"--